2014
DOI: 10.1016/j.humpath.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

IMP3 expression is associated with poor outcome and epigenetic deregulation in intrahepatic cholangiocarcinoma

Abstract: IMP3 is a fetal protein not expressed in normal adult tissues. IMP3 is an oncoprotein and a useful biomarker for a variety of malignancies and is associated with reduced overall survival of a number of them. IMP3 expression and its prognostic value for patients with intrahepatic cholangiocarcinoma (ICC) have not been well investigated. The molecular mechanism underlying IMP3 expression in human cancer cells remains to be elucidated. Here we investigated IMP3 expression in ICC and adjacent nonneoplastic liver i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The 53 studies involved 8,937 patients with different cancer types, including 6 studies of RCC,8,2529 6 lung cancer,9,30–34 4 oral cancer,10,3537 4 urothelial carcinoma,3841 4 ovarian cancer,16,17,42,43 3 hepatocellular carcinoma (HCC),4446 4 colorectal cancer,12,4749 3 prostate cancer,14,15,50 3 pancreatic cancer,5153 2 gastric cancer,11,54 2 intrahepatic cholangiocarcinoma (ICC),55,56 and one study each of tongue cancer,57 thyroid carcinoma,58 sacral chordoma,59 pilocytic astrocytoma and pilomyxoid astrocytoma (PA/PMA),60 neuroblastoma,61 meningioma,62 melanoma,63 breast cancer,64 giant cell tumor,65 bile duct carcinoma,66 esophageal carcinoma,67 and cervical cancer 13. A total of 25 studies involved Caucasians and 28 involved Asians.…”
Section: Resultsmentioning
confidence: 99%
“…The 53 studies involved 8,937 patients with different cancer types, including 6 studies of RCC,8,2529 6 lung cancer,9,30–34 4 oral cancer,10,3537 4 urothelial carcinoma,3841 4 ovarian cancer,16,17,42,43 3 hepatocellular carcinoma (HCC),4446 4 colorectal cancer,12,4749 3 prostate cancer,14,15,50 3 pancreatic cancer,5153 2 gastric cancer,11,54 2 intrahepatic cholangiocarcinoma (ICC),55,56 and one study each of tongue cancer,57 thyroid carcinoma,58 sacral chordoma,59 pilocytic astrocytoma and pilomyxoid astrocytoma (PA/PMA),60 neuroblastoma,61 meningioma,62 melanoma,63 breast cancer,64 giant cell tumor,65 bile duct carcinoma,66 esophageal carcinoma,67 and cervical cancer 13. A total of 25 studies involved Caucasians and 28 involved Asians.…”
Section: Resultsmentioning
confidence: 99%
“…Other mechanisms include DNA methylation and acetylation processes. Demethylated CpG islands characterize the IGF2BP3 promoter in intrahepatic cholangiocarcinoma cases, which were in stark contrast to normal liver tissues that were heavily methylated (Gao et al, 2014). More recently, a large-scale sequencing analysis of datasets of 15 cancer types from The Cancer Genome Atlas (TCGA) confirmed these data, showing an inverse correlation between the DNA methylation status of the IGF2BP3 promoter and IGF2BP3 mRNA expression (Panebianco et al, 2017).…”
Section: Regulation Of Igf2bp3 Expression In Cancermentioning
confidence: 96%
“…Studies have shown that 41% of ICC cases have a mutation in PTPN3, a protein tyrosine phosphatase family member. ICC patients with high levels of PTPN3 protein expression will have a significantly increased risk of postoperative recurrence [33], and IMP3, a novel oncoprotein expressed in 82% of ICC cases, is negatively correlated prognosis [34]. Sia et al used gene expression profiles and mutation analysis technology to classify ICC into two types.…”
Section: Molecular Typing Of Iccmentioning
confidence: 99%